The Social Life of Words: A Study of Slang and Identity Among Young Adults in Urban Brazil - Ribeiro, Ana Phaula (Mahogany Journal De Social, 2025)
This study investigates the use of slang as a tool for social identity construction among young adults in urban Brazil. The research aims to understand how slang functions within social groups, regional identities, and socio-economic contexts. Using ethnographic fieldwork and in-depth interviews with young adults from São Paulo, Rio de Janeiro, and Salvador, the study analyzes how slang is employed to signal group membership, assert regional pride, and negotiate social class distinctions. The findings show that slang serves as a marker of both inclusion and exclusion, reinforcing social boundaries. Regional variations in slang use reflect cultural differences between cities, while socio-economic factors influence how frequently and selectively slang is used. Gender also plays a role, with male participants using slang to assert masculinity, and females using it more relationally. Slang is further used as a form of resistance, particularly among marginalized groups, challenging mainstream cultural norms. This research contributes to the understanding of language as a key element in identity formation and social dynamics. It also offers new insights into how linguistic practices, such as slang, reflect the socio-cultural fabric of urban Brazil. Future research could examine the role of digital media in the evolution of slang and its influence on youth identities in the globalized world.